Исследование выбора оптимального места введения природных минеральных сорбентов при производстве сахара - Стеценко, Наталья Александровна; Мирошников, Олег Николаевич; Подобий, Елена Валерьевна; Бабич, О. А.; Райчук, Нина Николаевна (My University, 2011)
Показано, что наиболее эффективно снижают цветность растворов с небольшим содержанием сахарозы минералы монтмориллонит и глауконит. Adsorption properties of natural disperse minerals have been studied on the model sugar solutions. It was investigated that adsorbents increase effective of purification coloring substances solutions with a little concentration of sucrose – palygorskite and glauckonite.
Keywords: адсорбция; adsorption; природные дисперсные минералы; сахароза; эффект очистки; красящие вещества; natural disperses mineral; sucrose; effect of purification; coloring substances; кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів; кафедра технології оздоровчих продуктів